31.0k views
3 votes
2(d-3)+5(d+2) = 4(d+6)-11 ​

User Airtonix
by
7.7k points

1 Answer

3 votes

Given:-


  • \sf{2(d-3)+5(d+2) = 4(d+6)-11 }


\:

Solution:-


  • \sf{2(d-3)+5(d+2) = 4(d+6)-11 }


\:


  • \sf{2d - 6 + 5d + 10 = 4d + 24 - 11}


\:


  • \sf{2d + 5d - 4d = 24 - 11 + 6 - 10}


\:


  • \sf{7d - 4d = 13+6-10}


\:


  • \sf \: 3d = 19-10


\:


  • \sf \: 3d = 9


\:


  • \sf \: d = \cancel (9)/(3)


\:


  • \underline{ \boxed{ \sf{ \color{pink}d = 3}}}


\:

━━━━━━━━━━━━━━━━━━━━━━━━

Hope it helps! :)

User Anders Rask
by
7.0k points